Locating guest molecules inside metal-organic framework pores with a multilevel computational approach - Ernst, Michelle; Poręba, Tomasz; Gnägi, Lars; Gryn’ova, Ganna (The journal of physical chemistry. C, Energy, materials, and catalysis, 2023)
Molecular docking has traditionally mostly been employed in the field of protein-ligand binding. Here, we extend this method, in combination with DFT-level geometry optimizations, to locate guest molecules inside the pores of metal-organic frameworks. The position and nature of the guest molecules tune the physicochemical properties of the host-guest systems. Therefore, it is essential to be able to reliably locate them to rationally enhance the performance of the known metal-organic frameworks and facilitate new material discovery. The results obtained with this approach are compared to experimental data. We show that the presented method can, in general, accurately locate adsorption sites and structures of the host-guest complexes. We therefore propose our approach as a computational alternative when no experimental structures of guest-loaded MOFs are available. Additional information on the adsorption strength in the studied host-guest systems emerges from the computed interaction energies. Our findings provide the basis for other computational studies on MOF-guest systems and contribute to a better understanding of the structure-interaction-property interplay associated with them.
Gesehen am 23.03.2023
Published online26 December 2022